1989
DOI: 10.1111/j.1651-2227.1989.tb11297.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Morphological Effects of Human Hepatic Alkaline Phosphatase in a Neonate with Hypophosphatasia

Abstract: Acta Paediatr Scand Suppl 360: 154, 1989. Enzyme replacement-therapy for a severely affected premature boy (birthweight: 2 380 g, GA: 36 weeks) with hypophosphatasia was attempted by infusions of purified human hepatic alkaline phosphatase. Treatment (1.2 IU/kg/min) started at age three weeks and was repeated in weekly intervals until age 10 weeks, when the child died. Samples of alkaline phosphatase were diluted with 10 ml of physiological saline and infused over 30 min via an umbilical arterial catheter. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…The early attempts consisted in the intravenous administration of normal plasma, ALP-enriched plasma from patients with Paget bone disease, purified human liver ALP, or purified human placental ALP in infants with severe HPP, but were not successful [113][114][115].…”
Section: Enzyme Replacement Therapymentioning
confidence: 99%
“…The early attempts consisted in the intravenous administration of normal plasma, ALP-enriched plasma from patients with Paget bone disease, purified human liver ALP, or purified human placental ALP in infants with severe HPP, but were not successful [113][114][115].…”
Section: Enzyme Replacement Therapymentioning
confidence: 99%
“…Attempted enzyme replacement therapy (ERT) using intravenous (IV) infusions of ALP-rich plasma from Paget’s bone disease patients, purified human liver ALP, or purified human placental ALP failed to rescue severely affected infants [44,48–50]. From these studies, it was concluded that TNAP activity might need to be directed to the skeleton rather than simply enhanced in the circulation in order to prevent or reverse the pathophysiology of HPP [5,46].…”
Section: Introductionmentioning
confidence: 99%
“…The results of ERT, however, with intravenous infusion of plasma ALP or purified liver ALP in patients with hypophosphatasia have been disappointing [36][37][38][39][40]. Recently, one report suggested that continuous delivery of high dose of TNSALP to bone would be needed to induce physiological bone mineralization [41].…”
Section: Introductionmentioning
confidence: 99%